Revolution in Biblical Law: Some Reflections on the Role of Theory in Methodology - Jackson, Bernard S. (Journal of Semitic studies, 2005)
This is a review article of J. Van Seters, A Law Book for the Diaspora (2003), H.V. Bennett, Injustice Made Legal (2002), and A. Phillips, Essays on Biblical Law (2002). In the context of biblical law, there is a range of quite different types of theoretical starting point, and the books here under review make different choices amongst them: Van Seters opts for literary/compositional theory, Bennett for social theory, Phillips for a mix of comparative law and theology (though the balance of the book as a whole tends towards the latter). Examination of this collection of books — with some privilege given to Van Seters, the implications of whose work appear farthest-reaching for the field as a whole, and taking account of the non-programmatic character of Phillips' essays in their present form — may assist us in clarifying the underlying theoretical issues, issues which no one concerned with biblical law can afford to avoid.